2019
DOI: 10.3892/ijmm.2019.4075
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑223 attenuates LPS‑induced inflammation in an acute lung injury model via the NLRP3 inflammasome and TLR4/NF‑κB signaling pathway via RHOB

Abstract: Acute lung injury (ALI) and the more severe acute respiratory distress syndrome are common and complex inflammatory lung diseases. MicroRNAs (miRs) have emerged as novel gene regulatory molecules, serving a crucial role in a variety of complex diseases, including ALI. In the present study, the anti-inflammatory action of miR-223 on inflammation in ALI was demonstrated and the possible mechanism was further examined. In lipopoly-saccharide-induced ALI, the expression of miR-223 was reduced compared with that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 24 publications
(38 reference statements)
2
64
1
Order By: Relevance
“…The previous study found that the expression of miR-223 was enhanced after TLR4 was inhibited. This was in contrast to Yan et al [52], where downregulation of miR-223 induced the upregulation of TLR4, NF-κB, and NLRP3, while inhibiting TLR4 in vitro reduced the release of in vitro inflammatory factors following the downregulation of miR-223. This confirmed that miR-223 targets the role of TLR4 in the inflammatory response.…”
Section: Discussioncontrasting
confidence: 99%
“…The previous study found that the expression of miR-223 was enhanced after TLR4 was inhibited. This was in contrast to Yan et al [52], where downregulation of miR-223 induced the upregulation of TLR4, NF-κB, and NLRP3, while inhibiting TLR4 in vitro reduced the release of in vitro inflammatory factors following the downregulation of miR-223. This confirmed that miR-223 targets the role of TLR4 in the inflammatory response.…”
Section: Discussioncontrasting
confidence: 99%
“…Overexpressing miR-233 can attenuate LPS-mediated inflammation in the disease model. Interestingly, miR-233 has been also found to inhibit NLRP3 inflammasome by targeting rho-related GTPbinding protein RhoB (RHOB) [19]. In another study, miR-155 has been reported being elevated in bronchoalveolar lavage fluid (BALF) samples of ARDS patients.…”
Section: Discussionmentioning
confidence: 96%
“…Studies realized for understanding oral squamous cell carcinoma mechanisms and revealed that overexpression of both miR-223 and miR-22 suppressed NLRP3 inflammasome and NF- κ B signaling through ras homolog family member B (RHOB) and were considered as potential therapy targets [ 142 ]. Similar results were obtained studying cervical cancer pathogenicity, where it was observed that overexpression of miR-223 suppressed FOXO1, reduced proliferation of tumor cells, and regulated the inflammasome complex activation through the NF- κ B signaling pathway [ 143 ].…”
Section: Molecular Inflammatory Events During Cancer Development Amentioning
confidence: 99%